USM VICE-CHANCELLOR APPOINTED AS THE FIFTH PRESIDENT OF ASM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 28 December 2016 The ViceChancellor of Universiti Sains Malaysia (USM), Professor Datuk Dr. Asma Ismail has been appointed by His Majesty Yang diPertuan Agong XIV as the fifth President of the Academy of Sciences Malaysia (ASM) effective from today.